Velamentous cord insertion in monochorionic twin pregnancies: a step forward in screening for twin to twin transfusion syndrome and birthweight discordance? - Beatriz Branco Pinho (2022)
Introduction: Two major complications of monochorionic diamniotic (MCDA) twin pregnancies are twin to twin transfusion syndrome (TTTS) and birthweight discordance. The current screening ultrasound test for these pathologies combines the detection of nuchal translucency discrepancy and abnormal ductus venosus in at least one twin, in the first trimester. We aim to determine whether combining the presence of velamentous cord insertion in at least one twin increases screening efficiency. Methods: This was a multicentered retrospective cohort with a sample of 158 MCDA twin pregnancies followed at Centro Hospitalar Universitário São João and Asklepios Klinik Barmbek, during a 16-year period. Results: The combination of abnormal ductus venosus in at least one twin and nuchal translucency discrepancy is associated with the development of TTTS with an OR of 9.571, but not with birthweight discordance. The combination of these first trimester markers with velamentous cord insertion is not associated with the development of either outcome, but it shows a tendency towards the development of TTTS. Discussion: Despite the existence of a tendency for TTTS development in MCDA pregnancies with velamentous cord insertion, it was not statistically significant. Therefore, the addition of this marker to the first trimester screening would not effectively predict the development of birthweight discordance or TTTS. However, the screening test currently used increases about 9 times the risk of developing TTTS.